Development of Interactive Media Using the Genially Website With Pictured Vocabulary on Beginning Writing Materials for Grade I Elementary School Students - Sekar Arum Sari; Elfia Sukma; Desyandri Desyandri; Chandra Chandra (Journal of Educational Sciences, 2026)
This research aims to develop interactive learning media based on the Genially website using pictured vocabulary for beginning writing materials and to test its validity, practicality, and effectiveness for Grade I elementary school students. The study employed Research and Development method using the ADDIE model which consists of five stages: analysis, design, development, implementation, and evaluation. Data were collected through expert validation sheets, practicality questionnaires for teachers and students, and learning outcome tests. Subjects involved were Grade I students from four elementary schools in West Sumatra, Indonesia. Data analysis included validity, practicality, and effectiveness tests using N-Gain score. Results showed that the media was categorized as very valid with an average score of 89% based on assessment by material, media, and language experts. Practicality level reached 88.5% according to teachers and 81% according to students, indicating the media is easy to use and suitable for learning activities. Effectiveness test revealed that 90% of students experienced improvement in writing skills, with 40% in high improvement category and 50% in medium category. It is concluded that the developed media is valid, practical, and effective to support early writing skills, and can be used as an alternative learning resource in elementary schools.